2015
DOI: 10.1007/s13277-015-4278-1
|View full text |Cite
|
Sign up to set email alerts
|

Sodium glycididazole enhances the radiosensitivity of laryngeal cancer cells through downregulation of ATM signaling pathway

Abstract: The purpose of this study was to evaluate the radiation-enhancing effect of sodium glycididazole, and the corresponding mechanisms of action on laryngeal cancer cells. Two laryngeal cancer cell lines (Hep-2 and UT-SCC-19A) were irradiated with X-rays in the presence or absence of sodium glycididazole. Cell survival, DNA damage and repair, cell apoptosis, cell cycle distribution, expression of proteins related to cell cycle checkpoint, and apoptosis were measured. Significantly increased DNA damages, decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Interestingly, the enhancement of radiation-induced cell death by glycididazole was observed even in normoxia. A recent report by Zeng et al demonstrated the similar effect of glycididazole on normoxic laryngeal cancer cells and revealed significant downregulation of ataxia-telangiectasia mutated (ATM), p-ATM, CHK2, and p53 and the upregulation of MDM2 and Cdk2 after the combined treatment with glycididazole and X-irradiation, not only in hypoxic conditions, but also in normoxic conditions, and concluded that glycididazole has the potential to inhibit the ATM signaling response after X-irradiation (20). Although glycididazole is composed of a metronidazole dimer, to the best of our knowledge, there are no reports to demonstrate that metronidazole exerted radiation modifying effects, except for its oxygen-mimetic properties owing to the electron affinity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, the enhancement of radiation-induced cell death by glycididazole was observed even in normoxia. A recent report by Zeng et al demonstrated the similar effect of glycididazole on normoxic laryngeal cancer cells and revealed significant downregulation of ataxia-telangiectasia mutated (ATM), p-ATM, CHK2, and p53 and the upregulation of MDM2 and Cdk2 after the combined treatment with glycididazole and X-irradiation, not only in hypoxic conditions, but also in normoxic conditions, and concluded that glycididazole has the potential to inhibit the ATM signaling response after X-irradiation (20). Although glycididazole is composed of a metronidazole dimer, to the best of our knowledge, there are no reports to demonstrate that metronidazole exerted radiation modifying effects, except for its oxygen-mimetic properties owing to the electron affinity.…”
Section: Discussionmentioning
confidence: 94%
“…3). Only one study has examined the antitumor effect of glycididazole using the growth delay assay in a transplanted tumor model (20). The authors demonstrated the significant radiosensitizing potential of glycididazole in a xenografted Hep-2 tumor mouse model, but they employed a high dose of glycididazole (3x700 mg/m 2 /day).…”
Section: Discussionmentioning
confidence: 99%
“…While, miR-30a expression can increase IR-induced apoptosis and decrease IR-induced G2/M cell cycle arrest after 8 Gy IR. In response to IR induced DNA damage, phosphorylation of ATM can increase p53, either inducing DNA repair, cell cycle arrest (31), or apoptosis, thereby, maintain genomic stability (32) and this may also reduce the therapeutic effectiveness (33). p53 wild-type cell lines, when irradiating with ATM were downregulated, p53 cannot be retarded and lead to cell cycle checkpoint deficiency (1).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, in the middle stages of PAH, the upregulated ATM seems to prevent PA-SMCs from growth in order to slow down the development of PAH. It is well established that ATM signaling arrests proliferation and induces apoptosis [ 25 27 ]. In our study, inhibition of ATM signaling seemed to enhance PA-SMCs proliferation.…”
Section: Discussionmentioning
confidence: 99%